Sodium silicate and hexametaphosphate promote the release of (oxyhydr)oxide nanoparticles from corroding iron. Issue 5 (29th September 2022) - Trueman, Benjamin F.; Locsin, Javier; Doré, Evelyne; Hood, Kalli; Gagnon, Graham A.
Abstract : Sequestrants such as polyphosphate and sodium silicate are used to control iron precipitation in drinking water, but they may generate iron nanoparticles that increase lead mobility. Abstract : Sequestrants such as polyphosphate and sodium silicate are used widely to control iron precipitation in drinking water, but less is known about their impacts on iron corrosion scale. Here we characterize the nanoparticulate iron (oxyhydr)oxide suspensions that result from corroding cast iron coupons in solutions containing either sodium hexametaphosphate (3 mg P L −1 ) or sodium silicate (100 mg SiO2 L −1 ). We determined the elemental composition and size distribution of these suspensions using flow field-flow fractionation with ultraviolet, multielement, and multiangle light scattering detection. Both sequestrants yielded stable iron suspensions, and the pooled median radius of gyration at peak 57 Fe intensity was 22 nm, corresponding to a sphere-equivalent geometric diameter of 57 nm. The median Feret diameter and ASTM roundness were 50 nm and 0.4, respectively, as determined by transmission electron microscopy. Lead associated readily with iron nanoparticles, and in the hexametaphosphate suspension it associated preferentially with iron over free hexametaphosphate. Sequestrants then, may interact with iron corrosion scale to yield effective transport vectors for lead in drinking water systems, even when complexation of free lead by the sequestrant is negligible.